Performance Evaluation of the Circular Patch Antenna and Size Reduction with Slotted for WLAN Application - Surur Hassan Ali; Ali Khalid Jassim (Tikrit Journal of Engineering Sciences)
This paper presents a newly printed antenna with dimensions of (35 × 23 × 1.6) 〖mm〗^3. The proposed antenna consists of two parts, like plant leaves. A perforated flower has been inserted between these two leaves to enhance performance. These parts are printed on an inexpensive relative permittivity of 4.4 FR4 substrate material. The half-circumference of the circular cover was 17 mm. This work involves designing and simulating a circular microstrip patch antenna (CMPA) utilizing the Computer Simulation Technique (CST). It is designed to work exceptionally well at 5.599 GHz, with a gain of 2.031 dB, a reflection coefficient of -61.38dB, VSWR of 1.0017, and a total efficiency of about 78%, with an input impedance of 50.83 Ω and wide bandwidth of 724 MHz (5.2109 GHz–5.9351 GHz), making it suitable for WLAN applications.